SIMULTANEOUS IDENTIFICATION AND QUANTIFICATION OF HYDROQUINONE, TRETINOIN AND BETAMETHASONE IN COSMETIC PRODUCTS BY ISOCRATIC REVERSED PHASE HIGH PERFORMANCE LIQUID CHROMATOGRAPHY - maggadani, baitha PALANGGATAN; harmita; harahap, yahdiana; HUTABALIAN, HANA LILI NATASYA (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of this study was to obtain a simple and selective analysis method for determination of hydroquinone, tretinoin and betamethasone in whitening creams using reversed phase high-performance liquid chromatography (HPLC). Methods: Reverse Phase HPLC was used for method development, validation studies, and sample analysis. The method was optimized by evaluating several parameters that affects extraction of the sample, composition and types of mobile phase and also flow rate. Chromatographic separation was optimized on a C18 column [Sunfire, 250 x 4.6 mm, 5µm] utilizing a mobile phase consisting acetonitrile, methanol (90:10 v/v) and slightly addition of glacial acetic acid to reach pH 5in the ratio of 30: 50:20 v/v at a flow rate of 0.8 ml/min with UV detection at 270 nm and 350 nm. Results: The analytical methods fulfilled the validation requirements including accuracy, precision, linearity, selectivity, detection limits, and quantitation limits. The results showed the mean levels of hydroquinone, tretinoin and betamethasone in samples A and B were 1.78%; 0.07%; 0.12% and 2.00%; 0.07%; 0.13% respectively. Conclusion: The method was successfully applied for the determination of cosmetic formulation containing hydroquinone, tretinoin and betamethasone simultaneously. There were seven samples analyzed and two samples were positive containing hydroquinone, tretinoin, and betamethasone.